Development of the small-molecule antiviral ST-246®® as a smallpox therapeutic. (May 2011) - Grosenbach, Douglas W; Jordan, Robert; Hruby, Dennis E
Naturally occurring smallpox has been eradicated, yet it remains as one of the highest priority pathogens due to its potential as a biological weapon. The majority of the US population would be vulnerable in a smallpox outbreak. SIGA Technologies, Inc. has responded to the call of the US government to develop and supply to the Strategic National Stockpile a smallpox antiviral to be deployed in the event of a smallpox outbreak. ST-246 ®® (tecovirimat) was initially identified via a high-throughput screen in 2002, and in the ensuing years, our drug-development activities have spanned in vitro analysis, preclinical safety, pharmacokinetics and efficacy testing (all according to the ''animal rule''). Additionally, SIGA has conducted Phase I and II clinical trials to evaluate the safety, tolerability and pharmacokinetics of ST-246, bringing us to our current late stage of clinical development. This article reviews the need for a smallpox therapeutic and our experience in developing ST-246, and provides perspective on the role of a smallpox antiviral during a smallpox public health emergency.